Ecobrick sebagai Salah Satu Alternatif Menyelesaikan Permasalahan Sampah Plastik di Kampung Cokrokusuman Yogyakarta: Ecobrick as One of the Alternatives to Solve Plastic Waste Problems in Cokrokususman Village Yogyakarta - Salamah, Zuchrotus; Sasongko, Hadi; Nurusman, Arief Abdillah; Saputri, Andini Ika; Putri, Anggun Lintang Permata; Saroh, Vetin Yumita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The dense population of Cokrokusuman results in an increasing amount of waste, both organic and inorganic, one of which is plastic waste, therefore efforts need to be made to overcome this. The aim of this service is to introduce and increase knowledge and skills about ecobricks. The methods used are lectures, questions and answers, discussions, demonstrations and practice. This activity had a positive impact on the residents of Cokrokusuman, as can be seen from the evaluation results by comparing answers before and after the training. After the training, the community 100% understood the knowledge about ecobricks, materials and obstacles to making ecobricks. There are still 7.1% of people who do not understand the benefits and uses of ecobricks. The entire activity process was followed enthusiastically by all participants and gave satisfactory responses, the community was interested in making more diverse ecobrick creations.